Inhibition of acetylcholine receptor function by seronegative myasthenia gravis non-IgG factor correlates with desensitisation. - Spreadbury, I; Kishore, U; Beeson, D; Vincent, A (2005)
15% of myasthenia gravis (MG) patients do not have antibodies against the acetylcholine receptor (AChR). Some of these "seronegative" MG patients have antibodies against muscle specific kinase (MuSK), and many have a non-IgG factor that acutely inhibits AChR function in a muscle-like cell line, CN21. Here we show, using mainly one plasma negative for both AChR and MuSK antibodies, that the inhibitory effect of the non-IgG fraction correlates well with the desensitisation caused by 100 microM nicotine, and is found also when AChRs are expressed in a non-muscle cell line (HEK). Moreover, a similar effect was seen with M3C7-a monoclonal antibody against human AChR. The results suggest that, rather than acting indirectly as previously proposed, the SNMG factor may bind directly to an allosteric site that induces or enhances AChR desensitisation.